INTRAOPERATIVE PHOTODYNAMIC THERAPY FOR METASTATIC PERITONEAL TUMORS - E. A. Suleimanov (Issledovaniâ i Praktika v Medicine, 2016)
This review is devoted to the cytoreductive treatment of malignant tumors of the abdominal organs. The actuality of the issue is determined both by increase of the incidence of abdominal cancer in Russia and in majority of developed countries and by high rate diagnosis on late stages of disease. The methods of treatment of peritoneal carcinomatosis, based on possible effects on the secondary peritoneal tumors after surgical cytoreduction to reduce the risk of local recurrence and disease progression are described. These methods of additional intraoperative specific antitumor action include intraoperative radiation therapy, hyperthermic intraperitoneal chemotherapy, intraoperative photodynamic therapy characterized by differences in difficulty of performance, mechanisms of effect on tumor and healthy tissues, efficiency. Benefits, opportunities and possibilities of application of intraoperative photodynamic therapy (IOPDT) for secondary peritoneal tumors are described in details, the results of a number of domestic and foreign clinical studies are shown, the successful application of intraoperative photodynamic therapy in clinical oncology, which allows reducing the risk of secondary tumor lesions of the peritoneum significantly, is demonstrated. Photodynamic therapy – a method with high efficiency and almost no side effects and complications, based on the ability of photosensitizer to accumulate selectively and retain in the high proliferative tissues. The advantages of this type of treatment of patients with peritoneal carcinomatosis are a selective effect on the peritoneal carcinomatosis and on visually detected tumor tissue, high efficiency in patients with malignant tumors of the abdominal cavity and pelvis combined with surgical cytoreduction, minimal effect on normal organs and tissues of the patient, well tolerated procedure.